Vertical migration of the crab Carcinus maenas first zoea in an estuary: implications for tidal stream transport - Queiroga, Henrique (2015)
The first zoea of Carcinus maenas (L.) was intensively sampled in the Canal de Mira (Ria de Aveiro, Portugal) during the winter and spring of 1990. Each sampling period included a series of 25 h fixed-station plankton sampling cycles (12 in winter and 9 in spring), conducted at 1 station located in the lower part of the Canal. Plankton samples were collected every hour, at several depths along the water column, with the use of a pump. Hydrological measurements (salinity, temperature and current velocity and direction) were taken immediately before the collection of the plankton samples. The average depth of the zoeae changed in phase with the tide: larvae reached their highest position in the water column during ebb and their lowest during flood. The extent and phasing of the vertical displacements were such that the first zoea occupied a significantly higher position during the span of the ebb than during flood (p < 0.001). It was also demonstrated that the larvae were significantly closer to the surface during the night (p < 0.05). The pattern of vertical dispersion of the zoeae changed cyclically, with a period equivalent to the tidal half-cycle. Maximum aggregation usually occurred during periods of high current velocity and was independent from water stratification. These observations support the hypothesis that C. maenas first zoea performs an active vertical migration synchronised with tidal and daily cycles. Analysis of the zoeae instantaneous velocity showed that shifts of vertical position according to the phases of tide and day influenced their transport velocity, due to vertical differences of water velocity in the estuarine shear current system. During ebb the larvae were transported at a velocity that exceeded the vertically integrated water velocity; the reverse relationship was observed during flood (p < 0.001). The larvae were also transported faster during the night than during the day (p < 0.05). These results demonstrate that selective tidal stream transport can be generalised in the sense of a unidirectional transport mechanism in estuaries that can enhance exportation.